Effect of Organizational Culture and Organizational Commitment on Employee Performance with Job Satisfaction as Intervening Variable - Yusuf Ahmad Sudrajat; Arif Hartono (Publikasi Indonesia, 2022)
The study was conducted to know the meadiating effect of job satisfaction on the relationship between organizational commitment on employee performance. This research was used quantitave methods and questionannaire as a data collection tool. The population of this research was 1500 and the sample was 327 employees. Data collection techniques using a questionnaire with google form. Purposive random was used as a sampling methode, with purposive employees who have at least one year of service. F test, t-test, simple and multiple linear regression analysis and path analysis was used as analysis data methode. This research resulted that organizational culture has a postive influence on employee performance. Job satisfaction could mediate the relationship between organizational culture and employee performance. Job satisfaction could mediate the relationship between organizational commitment to employee performance.